2023
DOI: 10.1111/jcpp.13866
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation at birth and lateral ventricular volume in childhood: a neuroimaging epigenetics study

Abstract: BackgroundLateral ventricular volume (LVV) enlargement has been repeatedly linked to schizophrenia; yet, what biological factors shape LVV during early development remain unclear. DNA methylation (DNAm), an essential process for neurodevelopment that is altered in schizophrenia, is a key molecular system of interest.MethodsIn this study, we conducted the first epigenome‐wide association study of neonatal DNAm in cord blood with LVV in childhood (measured using T1‐weighted brain scans at 10 years), based on dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…More evidence in support of the epigenetic regulation/determination of language and handedness comes from a meta-analysis of the whole-blood DNA methylation of almost 4000 adults, reporting that the DNA methylation of CpG sites closed to the genetic variants associated with handedness were significantly linked to left-handedness compared to other CpG sites [ 124 ]. A more recent genome-wide DNA methylation analysis of neonate’s cord blood revealed that the methylation of KCTD , SDCCAG8 , and GLRX genes which are involved in brain functions are prospectively associated with the left ventricle volume at age 10 years [ 125 ], with an enlargement in SCZ (see Table 1 ).…”
Section: Interrupted Epigenetic Regulation Of Brain Laterality In Men...mentioning
confidence: 99%
“…More evidence in support of the epigenetic regulation/determination of language and handedness comes from a meta-analysis of the whole-blood DNA methylation of almost 4000 adults, reporting that the DNA methylation of CpG sites closed to the genetic variants associated with handedness were significantly linked to left-handedness compared to other CpG sites [ 124 ]. A more recent genome-wide DNA methylation analysis of neonate’s cord blood revealed that the methylation of KCTD , SDCCAG8 , and GLRX genes which are involved in brain functions are prospectively associated with the left ventricle volume at age 10 years [ 125 ], with an enlargement in SCZ (see Table 1 ).…”
Section: Interrupted Epigenetic Regulation Of Brain Laterality In Men...mentioning
confidence: 99%
“…An alternative approach to address developmental timing in multi-cohort studies involves strategic pooling of summary data at specific age ranges, as opposed to pooling all cohorts together regardless of age. This approach is commonly used in the PACE consortium (e.g., [6,37]), prioritize one epigenetic time point of interest (e.g., birth, because it is generally the time point with the largest sample size, or because of a focus on pregnancy exposures) and then query later DNAm assessments by (i) adopting a follow-forward approach, where significant CpG sites are selected for further analysis and tested at subsequent time points (e.g., [7,9,47]) or by (ii) conducting a completely new set of analyses at later developmental stages (e.g., running separate epigenome-wide analyses using DNAm at birth and DNAm in childhood in relation to the same child outcome [6,37]). While this strategy helps to partition analyses according to more developmentally-specific age groups, it does not directly quantify temporal changes in DNAm-brain associations, nor does it account for the potential non-linearity of this relationship over time.…”
Section: Challenge #2: Modeling Time-varying Dnam-brain Associations ...mentioning
confidence: 99%
“…DNA methylation (DNAm) is an epigenetic process that can regulate gene activity in response to both genetic and environmental influences [1,2], beginning in utero. While DNAm plays a key role in healthy development and function [3], alterations in DNAm have also been linked to the emergence of disease states, including brain-based disorders such as neurodevelopmental, psychiatric, and neurological conditions [4][5][6][7][8][9][10]. In addition, peripheral markers of DNAm are often more accessible to measure than several brain-based phenotypes.…”
Section: Introductionmentioning
confidence: 99%